Analytical model for the capacities of traditional Japanese timber frames with deep beams. (15th February 2022) - Li, Zherui; Isoda, Hiroshi; Kitamori, Akihisa; Nakagawa, Takafumi; Araki, Yasuhiro; Que, Zeli
Highlights: Analytical model the deep beam in the single-span timber frame. Derivation of the axial force generated on the deep beam under the frame deformation. Interaction between the deep beam and moment-resisting joints. Experimental verification of the resistance of a timber frame with deep beam. Abstract: In this study, the lateral resistance of a deep beam with beam-column joints in a timber frame applied in traditional Japanese residential houses and their possible interactions are discussed through experimental and theoretical analysis. When the frame deforms under lateral force, the rotation of the deep beam is constrained by the columns on both sides, and an axial force is generated on the deep beam along the diagonal direction. Via integration with beam-column joints, an estimation method of the lateral resistance of a traditional timber frame with a deep beam is proposed and confirmed with comparative tests. The results indicate that the resistance of the deep beam is affected by both the magnitude of the moment of the beam-column joints and the difference between the joint moments on the left and right sides of the beam. Meanwhile, the axial force on the deep beam is conducive to delaying the occurrence of ultimate failure of the beam-column joints.